Análise dimensional de malhas jersey de algodão com diferentes percentuais de elastano em sua composição - Oliveira, Gabriele Kyoko Takahashi de (2022)
Cotton Jersey fabrics have several properties, among the most important are flexibility and elasticity, which provide malleability and a better fit to body shapes, however these properties also affect the dimensions of the fabric, which can cause twists, deformities and elongations that directly influence the dimensional stability of garments. One way to improve this stability is the addition of elastane in the composition of the cotton knit, which is a combination that expands the number of applications of this knit in clothing, and can be used in several segments of the clothing industry. In addition to composition, other factors can change the dimensional stability of the fabric. In this work, a comparison of several physical properties was carried out using 3 Jersey knits (half knit) of cotton with elastane, varying the elastane linear density in 20, 40 and 70 Den. This study aimed to investigate the effects of the percentage of elastane on the properties of weight, density, structure, elongation, elasticity, tensile strength and dimensional stability. All experimental tests were performed according to brazilian standards, their results were calculated and their influence on the stability of cotton Jersey knitted fabric with different percentages of elastane was analyzed. From the results obtained, it was possible to prove that the elastane title has a direct influence on all the properties analyzed and also on the dimensional stability of cotton jersey knits with elastane. It was found that the increase in the percentage of elastane provides an increase in the values of the analyzed properties and in the dimensional stability of the analyzed knits.